Antibiotics alone instead of percutaneous drainage as initial treatment of large diverticular abscess - Elagili, Faisal; Stocchi, Luca; Ozuner, Gokhan; Kiran, Pokala Ravi (Springer Milan, 2015)
Background There are limited data assessing the effectiveness of antibiotics as sole initial therapy in patients with large diverticular abscess. The aim of our study was to compare outcomes of selected patients treated with initial antibiotics alone versus percutaneous drainage.